KAJIAN STRUKTURAL DAN KOMPARATIF FILM BEFORE TRILOGY DAN BOYHOOD KARYA AUTEUR: RICHARD LINKLATER - Saputra, Ellen Agustine (Dian Nuswantoro University, 2022)
The classic theory of authorship has sparked debate among academics, practitioners, and film critics for many years. In film education, the theory of auterism is widely discussed because it provides an interesting overview of film techniques and styles that is developed by an auteur. Richard Linklater is an auteur serving as director and screenwriter in many of his films. This study uses qualitative research methods with structural and comparative methods, where structural approach is used to deconstruct Richard Linklater’s film through the characters, themes, and visual styles (types of frames and camera movements). The comparative method is used to find similarities and differences in Before Trilogy and Boyhood, also to reveal Richard Linklater’s authorship style. To conclude the research, Richard Linklater is a collaborative auteur. In his experimental approach of filmmaking specificially in the making of Before Trilogy and Boyhood, Richard Linklater always worked collaboratively with actors or editors. The difference between Richard Linklater’s films can be seen through visual aspects of the film, on the contrary, in terms of narrative aspect, Before Trilogy and Boyhood do not have significant differences. Many similarities can be found throughout the narrative aspects of his films.